ANALYSIS OF HUMAN RESOURCE DEVELOPMENT TO INCREASE ONLINE SALES OF PAYU LEGI SHOP DURING THE COVID-19 PANDEMIC - Destiana, Riska; Habiburahman, Habiburahman (Universitas Mercu Buana, 2022)
From 2019 to 2020, Payu Legi's sales turnover is expected to drop. The purpose of this research is to determine how Payu Legi's online store sales are affected by human resource development. Only Payu Legi in Sukabumi, Bandar Lampung, is examined in this study. Payu Legi, the proprietors of small businesses, were the subjects of this survey. Five persons participated in this study: one owner and four staff. Descriptive data analysis is used in this form of qualitative study. All data gathered from the field, including observations, interviews, and data included in specific documents, are included in data gathering. To view the whole picture or just one component of the study, data is presented in an effort to do so. Payu Legi's online shop's sales have suffered as a consequence of its Human Resource Development efforts, according to a study on